2017
DOI: 10.2135/cropsci2016.07.0605
|View full text |Cite
|
Sign up to set email alerts
|

Season Progression, Ontogenesis, and Environment Affect Lespedeza cuneata Herbage Condensed Tannin, Fiber, and Crude Protein Concentrations

Abstract: Sericea lespedeza [Lespedeza cuneata (Dumont de Courset) G. Don., SL] is a perennial, warm‐season forage legume with wide adaptation, freeze tolerance, establishment ease, and persistence under grazing. It has high condensed tannin (CT) concentrations (g kg−1), which could be useful for methane mitigation and rumen bypass protein, as well as insect pest and gastro‐intestinal nematode suppression. However, CT concentration is variable. Our objective was to test CT, crude protein (CP), and fiber concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In a field study looking at the effect of season progression in repeatedly harvested and accumulated SL herbage, Muir et al . () confirmed that CT concentration in SL varied with edaphoclimatic conditions when measured throughout the season on regrowing or previously unharvested (unstressed) SL. These studies did not, however, compare season‐long harvest regimen effect on SL herbage CT concentration, a key factor in harnessing phenolic biological activity (Naumann et al .…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…In a field study looking at the effect of season progression in repeatedly harvested and accumulated SL herbage, Muir et al . () confirmed that CT concentration in SL varied with edaphoclimatic conditions when measured throughout the season on regrowing or previously unharvested (unstressed) SL. These studies did not, however, compare season‐long harvest regimen effect on SL herbage CT concentration, a key factor in harnessing phenolic biological activity (Naumann et al .…”
Section: Introductionsupporting
confidence: 61%
“…() found that CT concentrations were associated with maturity (reproduction) while Muir et al . (), with the same cultivar in the field, reported a less predictable pattern with season progression and ontogenesis.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Both concentration and composition can change with season Grabber et al, 2015;Muir et al, 2017), but accession differences tend to be much larger (Springer et al, 2002;Stringano et al, 2012). Importantly, environment did not affect the ranking of the CT traits of a few sainfoin accessions (i.e., there was no genotype ´ environment interaction) (Azuhnwi et al, 2013a ;Malisch et al, 2016); this demonstrates that there are opportunities for trait-directed breeding of new cultivars.…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 89%